1998
DOI: 10.1021/bi971484n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annexin V on the Structure and Dynamics of Phosphatidylcholine/Phosphatidylserine Bilayers:  A Fluorescence and NMR Study

Abstract: The consequences of the binding of annexin V on the structure and dynamics of PC/PS bilayers were studied by means of fluorescence polarization, 31P NMR, 2H NMR, and fluorescence recovery after photobleaching (FRAP). Even at complete coverage of the lipid bilayers by the protein, annexin V showed no influence on the lipid molecular packing and the acyl chain flexibility of both PC and PS. The fluorescence polarization of the probe DPH, the 31P NMR spectra, and deuterium quadrupolar splittings of P(d31)OPS rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 50 publications
9
59
0
1
Order By: Relevance
“…A slight ordering in the DMPA component above its phase transition, in the presence of protein, is suggested from the reduction in frequency at temperatures above the completion of the melting process. This minor change is consistent with peripheral protein binding and with a recent study of Saurel et al (12), who examined the consequences of AxV binding on the structure and dynamics of PC/PS bilayers using a variety of fluorescence and NMR-based experiments. They observed the appearance of slow motions (on the NMR time scale) in the lipid spectra, indicative of a decrease in lipid lateral diffusion, but observed no indication of changes in the lipid molecular packing and acyl chain flexibility in either of the lipid components.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A slight ordering in the DMPA component above its phase transition, in the presence of protein, is suggested from the reduction in frequency at temperatures above the completion of the melting process. This minor change is consistent with peripheral protein binding and with a recent study of Saurel et al (12), who examined the consequences of AxV binding on the structure and dynamics of PC/PS bilayers using a variety of fluorescence and NMR-based experiments. They observed the appearance of slow motions (on the NMR time scale) in the lipid spectra, indicative of a decrease in lipid lateral diffusion, but observed no indication of changes in the lipid molecular packing and acyl chain flexibility in either of the lipid components.…”
Section: Discussionsupporting
confidence: 88%
“…The effect of protein binding on the structure of mixed PC/PS vesicles and oriented bilayers was studied by fluorescence and NMR techniques (12). The presence of AxV led to the appearance of slow motions on the NMR time scale, indicating a reduction in the lipid diffusion rate.…”
mentioning
confidence: 99%
“…This also shows that the solution in the thin gap (∼ 8 nm for the 24-mer hybrid and ∼ 16 nm for the 48-mer hybrid, see below) between the bilayer patch and substrate surface is readily water-permeable so that salt ions are washed out immediately. Water accessibility was also checked by a cobalt quenching experiment (Saurel, Cezanne et al 1998). Co 2+ completely quenches fluorescence from Texas red labeled lipid, and in the case of solid supported lipid membranes, 54% of the fluorescence intensity is immediately quenched because Co 2+ in bulk solution cannot access the fluorescence dye in the bottom leaflet close to the substrate (Ajo-Franklin, Yoshina-Ishii et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Several annexin gene products have been shown to cause pronounced effects on lipid dynamics after Ca 2ϩ -dependent membrane binding. FRAP experiments have shown that the lateral diffusion rates of phospholipids are reduced by several orders of magnitude by annexin A4 or A5 binding (29,30). Furthermore, studies of spin-labeled lipids show that annexin A5 has found profound effects on the lipid fluidity gradient (31,32), which is naturally present in phospholipid bilayers (25).…”
Section: Discussionmentioning
confidence: 99%